2017
DOI: 10.12693/aphyspola.132.1045
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Structural and Magnetic Properties of the Cobalt-Nickel Alloys Fabricated in Various Electrolyte Solutions

Abstract: Cobalt-Nickel alloys have been widely used for decoration, in magnetic recording devices and corrosion resistance applications, etc. In this study, the influences of cobalt amount in electrolyte on the magnetic and structural properties of the electrodeposited Co-Ni alloys were investigated. An electrolyte solution, consisting of cobalt sulfate, nickel sulfate, nickel chloride and boric acid, was used in electrodeposition. The electrochemical investigation of Co-Ni alloys was completed using cyclic voltammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
1
Order By: Relevance
“…4,5) This composition-modulated Co-Ni laminated plating is available to produce by periodically varying stirring conditions during film formation in a single bath. Many of the studies [6][7][8][9][10][11][12] have been reported on the plating films consisted of the conventional metal multilayer films, but laminated structure producing required lamination in the plural different tanks or pulse electric plating as well as due to complicated manufacturing process, so that they are difficult to be put into industrial practice. In addition, there are many studies on the thickness of the constituent layers at the nanometer level, but there are few reports on thick films laminated with micrometer-level layers.…”
Section: Pp 426-432; J-stage Advance Published Date: August 23 2019)mentioning
confidence: 99%
“…4,5) This composition-modulated Co-Ni laminated plating is available to produce by periodically varying stirring conditions during film formation in a single bath. Many of the studies [6][7][8][9][10][11][12] have been reported on the plating films consisted of the conventional metal multilayer films, but laminated structure producing required lamination in the plural different tanks or pulse electric plating as well as due to complicated manufacturing process, so that they are difficult to be put into industrial practice. In addition, there are many studies on the thickness of the constituent layers at the nanometer level, but there are few reports on thick films laminated with micrometer-level layers.…”
Section: Pp 426-432; J-stage Advance Published Date: August 23 2019)mentioning
confidence: 99%
“…In this method, the thin film coating process is much more favorable than the others due to some reasons: 1) production simplicity, 2) variety of deposition materials, 3) low-temperature processing and 4) control of the bath composition. In the electrodeposition process, the electrocatalytic property of the solution and the amount of energy consumed varies depending on the production conditions and the materials in the bath composition [21][22][23]. Fabrication of thin films by electrodeposition method is influenced by such factors as solution concentration, pH value, current density, additives, deposition (cathode) potentials, solution temperature, mixing of solution, continuous or pulsed current of the deposition [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…CoNi alaşım ince film kaplama malzemelerin mikro ve nanoyapılı olarak üretimi için elektriksiz kaplama, elektrokimyasal depolama (elektrodepolama), sol-gel işlemi, spin kaplama, kimyasal buhar depolama, moleküler ışın epitaksi (MBE), manyetik alanda sıçratma (sputtering) gibi yöntemler kullanılmaktadır [9][10][11][12][13]. Bu yöntemler içerisinde en fazla kullanılanlardan biriside elektrodepolama sistemidir.…”
Section: Gi̇ri̇ş (Introduction)unclassified